1992
DOI: 10.1161/01.hyp.19.1_suppl.i96
|View full text |Cite
|
Sign up to set email alerts
|

Blunted natriuretic response to an acute sodium load in obese hypertensive dogs.

Abstract: Several studies support the premise that there is a strong relation between obesity and high blood pressure. Although the mechanism for obesity-related hypertension has not yet been fully elucidated, recent studies have suggested that abnormalities in renal sodium handling may be involved in the pathogenesis of obesity-induced hypertension. The purpose of the present study was to determine the effects of an acute saline load on renal excretory function in dogs with obesity-induced hypertension and in normotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
5
10
0
2
Order By: Relevance
“…Thus, a longer period of overfeeding, with greater body fat content of the animals may have changed the results observed following energy restriction in insulin and glucose, as well as other parameters measured in this study. While the decrease in blood pressures with weight reduction with either diet was expected (33), there was not a significant increase in blood pressure with weight gain during the 9-week ad libitum feeding period as we (40) and others (33) have previously reported in the dog. This may have been due to the fact that the gain in body weight following 9 weeks of the moderately high-fat diet was slight and only two of the animals had high levels of body fat (Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…Thus, a longer period of overfeeding, with greater body fat content of the animals may have changed the results observed following energy restriction in insulin and glucose, as well as other parameters measured in this study. While the decrease in blood pressures with weight reduction with either diet was expected (33), there was not a significant increase in blood pressure with weight gain during the 9-week ad libitum feeding period as we (40) and others (33) have previously reported in the dog. This may have been due to the fact that the gain in body weight following 9 weeks of the moderately high-fat diet was slight and only two of the animals had high levels of body fat (Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…4 -910 We have also recently reported that the obese hypertensive dog excretes significantly less sodium and water than normotensive control dogs in response to an acute saline load. 11 Furthermore, research indicates that obese hypertensive patients exhibit abnormal renal sodium handling. 14 Thus, it appears that the regulatory mechanisms responsible for control of sodium excretion and extracellular fluid volume may be altered in obesity-associated hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…46 We have recently demonstrated that the natriuretic response to an acute sodium load is significantly attenuated in obese dogs. 7 Although the exact mechanism responsible for the blunted natriuretic response to an acute sodium load in obesity-hypertension is unknown, abnormalities in sodium-retaining systems such as renin-angiotensin and renal sympathetic nervous systems may be involved. 8 To quantify the role of renal nerves in the blunted response to an acute sodium load in obese dogs, we examined the changes in renal hemodynamics and sodium excretion in separate innervated and denervated kidneys simultaneously within the same dog.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, we have recently demonstrated that the natriuretic response to an acute sodium load is significantly attenuated in obese dogs. 7 Although the exact mechanism responsible for the blunted natriuretic response to an acute sodium load in obesity hypertension is unknown, abnormalities in sodiumretaining systems such as renin-angiotensin and renal sympathetic nervous systems may be involved. 8 A possible role for renal nerves is supported by studies indicating that obesity is associated with increased activity of the sympathetic nervous system.…”
mentioning
confidence: 99%